Factors Shaping the Capability of Agribusiness Production in the Volcano Disaster Prone Zone - Iwan Hermawan; Sartono Sartono; Gita Hindrawati (Research Synergy Foundation, 2022)
Agroindustry regions with the potential for volcano disasters are strategic to be developed. The long-term post-eruption impact of volcanic ash benefits agricultural crops in the surrounding area. However, in the short term, it will impact crop damage and damage to infrastructure that disrupts production activities and marketing of agricultural products. This paper aims to find out the factors in creating the capabilities of agribusiness actors in the prone zone to the Merapi volcano disaster. These factors are attributes of the production capability construct relevant to a fast recovery process scheme that encourages the availability of production continuity areas as part of disaster management. This paper discusses the factors that form the capability of agriculture production in Magelang regency adjacent to an active volcano, Mount Merapi, with a multivariate approach using factor analysis in the agribusiness zone. The sample of this research is 100 respondents of farmers and agribusiness owners. The sampling technique used was cluster random sampling, by taking sample data from 21 districts in Magelang Regency. The discussion in this paper determines that four factors shape agricultural capability in disaster-prone zones: support for production modernization, knowledge management, communication convergence, and change management. These four components will contribute in the context of scientific disaster management to productivity in the agroindustry area.